PENGARUH STRUKTUR MODAL, EFISIENSI OPERASIONAL, RASIO LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS BANK DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Josua Stanley; Nagian Toni; Hendry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of capital structure, operational efficiency, liquidity ratio, and firm size on the profitability of national private banks in Indonesia, with Good Corporate Governance (GCG) as a moderating variable. This research employs a quantitative approach using secondary data derived from annual financial statements and GCG implementation reports of national private banks listed on the Indonesia Stock Exchange during the 2018-2023 period. The research sample consists of 11 national private banks with a total of 66 observations. Profitability is measured using Return on Assets (ROA), capital structure is measured by the Debt to Equity Ratio (DER), operational efficiency by the Operating Expense to Operating Income ratio (BOPO), liquidity ratio by the Loan to Deposit Ratio (LDR), and firm size by the natural logarithm of total assets. Data analysis was conducted using panel data regression with moderation testing. The results indicate that capital structure and operational efficiency have a significant effect on bank profitability, while the liquidity ratio and firm size do not have a significant effect. Furthermore, Good Corporate Governance is unable to moderate the effect of capital structure and operational efficiency on profitability, but is able to moderate the effect of the liquidity ratio and firm size on bank profitability. These findings suggest that the role of GCG in enhancing bank profitability is contextual and depends on the characteristics of the moderated variables.